2022
DOI: 10.1039/d1ta10896d
|View full text |Cite
|
Sign up to set email alerts
|

Zero fire battery concept: water-in-battery

Abstract: The energy storage system (ESS) safety issue caused by battery thermal runaway is becoming severe, and its solution has not yet been optimized. Herein, we propose the concept of a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Electrochemical energy storage (EES) devices, typically including high-energy-density batteries and high-power-density supercapacitors, are indispensable for clean electricity supply. [1][2][3][4][5][6][7] Realizing EES with outstanding low-temperature tolerance is crucial in many specialized elds (e.g., −60 °C for polar explorations, −50 °C for aeronautical applications, and −30 °C for electric vehicles). [8][9][10] However, the electrochemical performance of current commercial EES devices decays sharply with the drop in environmental temperature to below −40 °C, resulting in weak ion dynamics, poor capacity retention, and even complete failure of energy storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical energy storage (EES) devices, typically including high-energy-density batteries and high-power-density supercapacitors, are indispensable for clean electricity supply. [1][2][3][4][5][6][7] Realizing EES with outstanding low-temperature tolerance is crucial in many specialized elds (e.g., −60 °C for polar explorations, −50 °C for aeronautical applications, and −30 °C for electric vehicles). [8][9][10] However, the electrochemical performance of current commercial EES devices decays sharply with the drop in environmental temperature to below −40 °C, resulting in weak ion dynamics, poor capacity retention, and even complete failure of energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical energy storage (EES) devices, typically including high-energy-density batteries and high-power-density supercapacitors, are indispensable for clean electricity supply. 1–7 Realizing EES with outstanding low-temperature tolerance is crucial in many specialized fields ( e.g. , −60 °C for polar explorations, −50 °C for aeronautical applications, and −30 °C for electric vehicles).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 15 demonstrated that battery heat management by water immersion is possible by coating the surface of a cylindrical battery with epoxy-paraffin-graphite composite materials. Bae et al 16 experimentally demonstrated the fire suppression and thermal management capabilities of water-immersion batteries. However, insulating each cell by coating or sealing is inefficient, while batteries may be damaged during the insulation process.…”
mentioning
confidence: 99%
“…5–7 Therefore, aqueous batteries can be a solution for the ESS due to the non-flammability of the aqueous electrolyte. 8…”
mentioning
confidence: 99%
“…[5][6][7] Therefore, aqueous batteries can be a solution for the ESS due to the non-ammability of the aqueous electrolyte. 8 A vanadium redox ow battery (VRFB) has been widely utilized among various aqueous batteries due to the greatest number of developments and commercialization due to high exibility, long cyclability, and excellent efficiency. [9][10][11] However, vanadium has the disadvantage of high cost, accounting for half the price of the total VRFB system.…”
mentioning
confidence: 99%